Hallucinations Research and Practice - Blom, Jan Dirk; Sommer, Iris E.C (Springer New York : Imprint: Springer, 2012)
Hallucinations continue to fascinate people throughout the world. The mere possibility of perceiving things that are not there is the stuff that campfire tales are made of. It is one thing to be in a dream state, to be asleep and to conjure up people, scenes, and landscapes that do not actually exist, but it is quite another to hallucinate: to be wide awake, and yet hear that ethereal music, see those costumed figures strolling by, smell the roses that used to grow in your grandfather's garden, feel his hand upon your shoulder, sense his presence somewhere near -- and to be the only one able to experience it. In this book, 44 international neuroscientific experts join forces to present a state-of-the-art overview of hallucinatory phenomena, ranging from visual, auditory, olfactory, gustatory, and bodily hallucinations to less well-known phenomena such as synaesthesias, musical hallucinations, hallucinated pain, autoscopic phenomena, phantom sensations, sensed presences, and compound hallucinations attributed to djinns. Additional sections deal with the conceptual, phenomenological, and neuroscientific aspects of those phenomena, and offer an update on contemporary treatment possibilities ranging from pharmacotherapy to electroconvulsive therapy, transcranial magnetic stimulation, cognitive-behavioral therapy, and self-help groups. This book is essential reading for neuroscientists, neurologists, psychiatrists, general physicians, psychologists, historians of science, and philosophers professionally involved in the diagnosis, treatment, and scientific study of hallucinations. Jan Dirk Blom, M.D., Ph.D., is the Director of the Psychiatric Residency Training Programme of the Parnassia Bavo Group in The Hague, and holds a position as Assistant Professor of Psychiatry at the University of Groningen. Iris E.C. Sommer, M.D., Ph.D., is Professor of Psychiatry at the University Medical Center Utrecht and the Rudolf Magnus Institute of Neuroscience, Utrecht, the Netherlands.  .